MacBook Pro - Miser, Brad (Portable genius., 2011)
Looks at the features and functions of the MacBook, covering such topics as creating and managing user accounts, sharing files, using MobileMe, configuring iChat, setting up iCal, adding data storage, and running Windows applications.